Efektivitas Penerapan Sistem Informasi Manajemen di SMPS Galih Agung Deli Serdang dalam Peningkatan Kualitas Pendidikan - Lubis, Harun; Aulia, Tirta Yogi (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Lhokseumawe, 2024)
This study aims to describe and evaluate the effectiveness of the implementation of the Management Information System (MIS) at SMPS Galih Agung Deli Serdang in improving the quality of education. The research employs a descriptive qualitative method with a case study approach, collecting data through interviews, observations, and documentation studies. The results indicate that the implementation of the school website and the Academic Information System (Dapodik) has enhanced information accessibility and management efficiency. The school website provides a real-time platform for students, parents, and teachers to access important information, while Dapodik speeds up academic administrative processes such as recording student attendance and grades. The implementation of these systems has facilitated information access, improved administrative efficiency, and positively impacted lesson planning and parental involvement in education. The study also identified challenges in resource management and monitoring, such as a lack of guidelines for activity planning and an imbalance in staff workload. The training provided has improved staff understanding of planning, and the redistribution of teaching duties has reduced workload-related complaints. The implications of this research suggest that effective management information system implementation can enhance educational quality by facilitating information access, improving administrative efficiency, and supporting a more structured learning process.